SISTEM INFORMASI AKADEMIK SMA KATOLIK BLORA BERBASIS WEB SMA ACADEMIC INFORMATION SYSTEM BASED ON WEB KATOLIK BLORA (Information Technology and Telematics, 2014)
Abstract–Academic Information System is a system that gives information about academic data services. The existence of academic information system is very important in helping to provide information to students. In this case Blora Catholic high school used as a pleace of research, because the informatin in the school system is not managed properly, making it difficult to process the existing academic data, as well as updating the teacher data, student data update, update students grades.The purpose of this research is to simplify the current process or to update the teacher data, student data and student grades to process the data, improving the security of student data so that data security is guaranted students. The system development using SDLC (System Development Life Cycle) learning sysyem catholic high school academic information Blora web based program using PHP and MySQL database storage. Keyword: web, academic information system, SDLC, php, MySQL